Respon Pertumbuhan dan Hasil Tanaman Kubis bunga (Barassica oleracea L) Akibat Pemberian Cangkang Telur Ayam - Hayatul Rahmi; Marudut Tua; Yayu Sri Rahayu (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
Flower cabbage is a vegetable crop that is widely consumed by the people of Indonesia. For growth, it can be helped by providing egg shells that are environmentally friendly when compared with chemical fertilizers. This study used a Randomized Block Design with five doses of eggshell treatment (0,6,12,18,24 grams / plant) with five replications each. The results of the research are: The application of eggshell fertilizer which has a significant influence on the number of leaves aged 35 dd, and on the flower weight per plant. And the dose of eggshell fertilizer that gives the best treatment E (2.0 g / plant) with a yield of 301.53 g / plant.